Scheduling Parallel Applications on Heterogeneous Distributed Systems - Xie, Guoqi; Zeng, Gang; Li, Renfa; Li, Keqin (Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on scheduling algorithms for parallel applications on heterogeneous distributed systems, and addresses key scheduling requirements - high performance, low energy consumption, real time, and high reliability - from the perspectives of both theory and engineering practice. Further, it examines two typical application cases in automotive cyber-physical systems and cloud systems in detail, and discusses scheduling challenges in connection with resource costs, reliability and low energy. The book offers a comprehensive and systematic treatment of high-performance, low energy consumption, and high reliability issues on heterogeneous distributed systems, making it a particularly valuable resource for researchers, engineers and graduate students in the fields of computer science and engineering, information science and engineering, and automotive engineering, etc.The wealth of motivational examples with figures and tables make it easy to understand. .